Structural assessments of kerogen-rich oil shale from the Central Kongo formation by solid-state .sup.13C nuclear magnetic resonance and thermal processes - Bouamoud, Rajaa; Mulongo-Masamba, Raphael; El Hamidi, Adnane; Halim, Mohammed; Arsalane, Said (Journal of thermal analysis and calorimetry, 2022)
Oil produced from the organic matter-rich sedimentary rocks pyrolysis processes represents one of the most promising and available unconventional fossil fuel reserves that can fill the energy deficit in the near future. In the present study, the kerogen-rich oil shale originated from the Central Kongo (CK) in Democratic Republic of the Congo was subject of numerous characterization studies, such as .sup.13C cross polarization/magic angle spinning nuclear magnetic resonance (.sup.13C CP/MAS NMR), simultaneous thermogravimetry/differential thermal analysis (TG/DTA) and fast pyrolysis combined with gas chromatography/mass spectrometry (Py-GC/MS). .sup.13C NMR results indicate that the kerogen carbon skeleton is mainly of aliphatics with methylene chains, in agreement with the molar ratio H/C of 1.71. The predominance of aliphatics over aromatics is indicative of an immature type I kerogen. In addition, thermal analysis revealed a single and narrow pyrolysis process of kerogen at temperature below 456 °C, reflecting the immature type I kerogen in CK oil shale. The results of fast Py-GC/MS show that the studied sample is primarily of aliphatic carbons (n-alkane/n-alkene) and formed of short methylene chains with maximum carbon distribution at C15. The minor components of C20 + suggested marine origin of kerogen with an anoxic reductive environment during the diagenesis of the source rock.